MENINGKATKAN PRESTASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE “INDEX CARD MATCH” - Rini Mei Hastuti; Wakhudin (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to analyze the effect of the Index Card Match learning model on students' Mathematics learning achievement and collaboration skills. The study used a Quasi Experimental with a One Group Pretest-Posttest design. The population of this study were sixth grade students in the Permadani Cluster, Purwojati District, Banyumas Regency, Central Java. Sixth grade students of SDN 1 Gerduren were selected as samples in this study through a simple random sampling technique. Hypothesis testing used the t-test, namely the paired sample t-test assisted by the SPSS 26 application. Mathematics learning achievement data were obtained through two tests, namely pretest and post-test. Collaboration skills data were obtained through observation and questionnaires. The calculation of the questionnaire used a Likert scale. Testing the research hypothesis with a paired sample t-test obtained a significance value of 0.003 or <0.05, which means that H0 is rejected. This means that Mathematics learning using Index Card Match has an effect on students' learning achievement. While the calculation on the Likert scale shows that the assessment interval for the effect of the index card match learning model on students' collaboration skills is 86.14%. This indicates that as many as 86.14% of students stated that they strongly agreed that their collaboration skills in Mathematics learning had changed for the better.